Incidencia de la escasa educación sexual en los embarazo precoces en las adolescentes del 10 mo. año de educación básica del Colegio Nacional Mixto Atahualpa de la ciudad de Machala periodo lectivo 2012-2013. - Luna Celi, Yolanda Elizabeth (2013)
This research focused on the impact of poor sex education in early teenage pregnancy Joint Atahualpa National College, problematic context that arises in the educational process, for which we proceeded to the investigation, taking into account that, to the extent that work to improve sex education will decrease early pregnancies and improve the educational process of the students.